36 stratagems & applications - Soe Thiha @ Nyan Lin Htun (Nanyang Technological University, 2020)
The 36 stratagems were accepted to evolve from hundreds of years of ancient Chinese warfare among warlords, kings, aristocrats fighting for power, for land, or for sovereign kingdom, yet still very widely recognized to be useful in all areas including policy making, changing healthy life styles, persuasive negotiations etc.